Ready, set, go! Motivation and lifestyle habits in parents of children referred for obesity management. Issue 5 (14th November 2014) - Maximova, K.; Ambler, K. A.; Rudko, J. N.; Chui, N.; Ball, G. D. C.
Summary Background Parents play a fundamental role in helping children with obesity to make and maintain healthy lifestyle changes. Objective This study aimed to characterize stages of engagement to change nutrition and physical activity habits among parents whose children with obesity were enrolled in obesity management and examine differences in parents' own nutrition and physical activity habits according to their stage of engagement. Methods Medical records of 113 children (body mass index [BMI] ≥95th percentile) enrolled in an outpatient weight management clinic were reviewed for baseline (cross‐sectional) data. Parents completed the Weight Loss Behavior–Stage of Change Scale to assess the degree of engagement in making healthy changes to their lifestyle behaviours. Latent class analysis was used to classify parents into distinct clusters by grouping individuals with similar ratings of stages of engagement regarding nutrition‐ and physical activity‐related behaviours. Results Parents' engagement in healthy lifestyle behaviours varied (more engaged [n = 43]; less engaged [n = 70]). A greater proportion of parents in the more engaged group was in action and/or maintenance stages of changing their lifestyle habits. The more engaged group was less overweight than the less engaged group (BMI = 28.5 vs. 33.3 kg m−2; P < 0.05). Further, the more engaged group consumed fewer total calories, calories from fat, trans fat and carbohydrates vs. their less engaged peers (P < 0.05). Compared with the less engaged group, the more engaged group consumed more daily servings of vegetables and fruits (4.9 vs. 3.9, P < 0.05) and accumulated more steps per day (9130 vs. 7225; P < 0.05). The more engaged group was also more likely to meet daily recommendations for vegetable and fruit intake (48.8 vs. 24.3%; P < 0.05) and physical activity (42.9 vs. 22.9%, P < 0.05). Conclusions Parents of children with obesity varied in their degree of engagement in making healthy changes to their lifestyle behaviours, and those categorized as more engaged already demonstrated positive lifestyle behaviours. Information regarding parents' degree of engagement in healthy behaviours can inform clinical recommendations, especially when parents represent the primary agents of change in families trying to manage paediatric obesity.